Synthesis and Characterization of Zinc Oxide Nanoparticles for Antibacterial Applications - S. Naseem Shah; S. Imran Ali; S. Rizwan Ali; M. Naeem; Yasmeen Bibi; S. Rehan Ali; S. Masood Raza; Yousuf Khan; Sikander Khan Sherwani (Journal of Basic & Applied Sciences, 2016)
ZnO nanoparticles are synthesized for antibacterial applications by a simple co-precipitation method. X-ray diffraction (XRD) reveals that the synthesized ZnO has hexagonal crystal structure with mean crystallite size of 29 nm. Scanning electron microscopy (SEM) and Energy dispersive x-ray spectroscopy (EDX) shows pure ZnO with uniform morphology. UV–VIS absorption spectroscopy yield an absorption edge in the range 300-400 nm which corresponds to a band gap energy of 3.50 eV. Antibacterial activity of ZnO nanoparticles is tested against gram positive and gram negative bacteria by using agar-well method. These ZnO nanoparticles are found to be strongly antimicrobial as they effectively prevent the growth of many test microorganisms with a small minimum inhibitory concentrations (MIC) 80 – 280 µg/ml.